Structural performance of masonry prisms, wallettes and walls containing high volume of industrial by-products – Sustainable housing perspective. (11th October 2021) - Nayaka, R. Ramesh; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Fonseca, Fernando S.; Banerjee, Anish
Highlights: Waste derived from palm oil and steel industries has potential to be used as cement and aggregates replacement. The structural performance of the environmentally friendly masonry products is very good. Minimal reduction of compressive strengths was observed in innovative masonry elements. Structural performance of masonry products satisfactory to utilise in masonry structure for sustainable housing. Abstract: Masonry buildings are in great demand in developing countries due to the need for sustainable and affordable housing. However, increased materials costs and carbon emissions associated with the production and use of conventional masonry products and need for higher standard of living have led to a steady increase in embodied energy use and costs of construction. There have been worldwide efforts to replace some of the traditional masonry components such as cement with industrial and agricultural byproducts in order to reduce cost and embodied energy. In this study, the structural performance and behavior of innovative masonry, i.e., masonry structural elements that incorporated industrial by-products, were analysed. The characteristics of innovative masonry were evaluated by determining its compressive strength in prisms and wallette structures, tensile and shear strengths in wallettes and walls, flexural strength in masonry beams, and axial compression strength in reinforced and unreinforced masonry columns. The moduli of elasticity of innovative masonry products were also determined and compared to that of conventional masonry. The tests showed that the strength of innovative masonry was between 70 and 90% that of conventional masonry, which can be considered adequate and satisfactory for construction applications.